Dehydration of Biomass-derived Butanediols over Rare Earth Zirconate Catalysts - Asami Matsuda (Catalysts, 2020)
The aim of this work is to develop an effective catalyst for the conversion of butanediols, which is derivable from biomass, to valuable chemicals such as unsaturated alcohols. The dehydration of 1,4-, 1,3-, and 2,3-butanediol to form unsaturated alcohols such as 3-buten-1-ol, 2-buten-1-ol, and 3-buten-2-ol was studied in a vapor-phase flow reactor over sixteen rare earth zirconate catalysts at 325 °C. Rare earth zirconates with high crystallinity and high specific surface area were prepared in a hydrothermal treatment of co-precipitated hydroxide. Zirconates with heavy rare earth metals, especially Y2Zr2O7 with an oxygen-defected fluorite structure, showed high catalytic performance of selective dehydration of 1,4-butanediol to 3-buten-1-ol and also of 1,3-butanediol to form 3-buten-2-ol and 2-buten-1-ol, while the zirconate catalysts were less active in the dehydration of 2,3-butanediol. The calcination of Y2Zr2O7 significantly affected the catalytic activity of the dehydration of 1,4-butanediol: a calcination temperature of Y2Zr2O7 at 900 °C or higher was efficient for selective formation of unsaturated alcohols. Y2Zr2O7 with high crystallinity exhibits the highest productivity of 3-buten-1-ol from 1,4-butanediol at 325 °C.